Gender and performance in Shakespeare's problem comedies - McCandless, David Foley (Drama and performance studies., 1997)
"Composed at a critical moment in English history, Shakespeare's "problem plays"--All's Well That Ends Well, Measure for Measure, and Troilus and Cressida - dramatize a crisis in the sex-gender system. They register a male dread of emasculation and engulfment, a fear of female authority and sexuality. In these plays males identify desire for a female as dangerous and unmanly; females contend and confound traditional femininity. Male authority, even male ideas of the heroic, suffers in the face of a female's disruptive sexual power. By resisting comic closure, these plays leave uncontained the subversions of gender that comedies for the most part successfully hold in check." "David McCandless follows the drama of gender enacted in these plays. His approach weds a theoretically engaged textual analysis to the dynamics of performance. He adopts the perspective not of expert spectator but of practitioner, bringing directorial modes of inquiry to his analysis. While drawing upon the performance histories of the problem comedies, he exploits his own experience as a director in dramatizing and theorizing the enactment of gender. The book provides a unique and invigorating example of how performance criticism can illuminate these difficult, sometimes overlooked tragicomedies."--Jacket.